Managing innovation integrating technology - Mohd Sam, Mohd Fazli; Mohd Adnan, Shayuti (Penerbit UTeM Press, 2024)
Through the Managing Innovation program, graduate and undergraduate students can acquire the specialized knowledge and fundamental skills required to manage innovation, technology, and new product development successfully. The integrated, evidence-based paradigm for innovation management in the book is supported by the authors extensive experience in both real-world management practice and the most recent scholarly research. Managing Innovation is a complete framework for considering innovation from a range of technological, market, and organizational perspectives, even though it incorporates the latest developments in innovation management. Because of its strong, evidence-based, and practical approach, this is a must-read for anybody interested in studying or working in innovation.